2020
DOI: 10.46490/bf426
|View full text |Cite
|
Sign up to set email alerts
|

The soil fungal communities in nurseries producing Abies alba

Abstract: Silver fir is an important forest-forming species in the mountain and upland parts of Poland. It was determined that fir lost the possibility of spontaneous return to the forests of the region. That is why the Polish State Forests has launched a programme to restore its resources in the Sudetes. Until now, fungi and their relationship with fir have not been fully addressed in the Sudetes Restitution Programme, therefore this study was undertaken. The aim of this study was to determine the species composition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Basidiomycota taxa did not dominate in every fungal community in the soil. However, in most trials, the Basidiomycota group's fungi were dominant, confirmed by Behnke-Borowczyk et al (2020).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Basidiomycota taxa did not dominate in every fungal community in the soil. However, in most trials, the Basidiomycota group's fungi were dominant, confirmed by Behnke-Borowczyk et al (2020).…”
Section: Discussionmentioning
confidence: 74%
“…Results were subjected to bioinformatic analysis according to Behnke-Borowczyk et al (2020). Obtained sequences were compared using the BLAST algorithm with the reference sequences from the NCBI database (https://www.ncbi.nlm.nih.gov).…”
Section: Methodsmentioning
confidence: 99%
“…The development of molecular methods, including next-generation sequencing, has enabled the full spectrum of microorganisms from tested samples to be identified and quantified. Consequently, this progress in technology has changed the possibilities for research in this field, from just observing a single taxon to monitoring the whole community and facilitating the identification of the interactions between functional and phylogenetic groups [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…When taking ongoing climate change into account, these attributes could result in not only a stronger limit on range, but also a strong effect on natural regeneration and growth, making this species with its discrete provenances adapted to specific mountain conditions more prone to extinction. For this reason, the State Forests (Poland) introduced a programme of artificial restoration of valuable and unique fir resources in the Sudeten Mountains[2][3][4][5][6][7][8][9][10] .Both biotic and abiotic factors strongly affect plant growth in forest stands, but even more significantly regulate seedling growth in the initial stages, even in forest nurseries11,12 . High soil fertilisation and overwatering could play a large role in seedlings' inability to adapt in order to overcome future water deficits, but can also positively result in a root and associated fungal community composition characterised by acquisitive ability within competitive mountain environments[13][14][15] .…”
mentioning
confidence: 99%